Safety and efficacy of intravenous immunoglobulin (Flebogamma® 10% DIF) in patients with immune thrombocytopenic purpura. (30th November 2018) - Apte, Shashikant; Navarro-Puerto, Jordi; Damodar, Sharat; Ramanan, Vijay; John, Joseph; Kato, Giraldo; Ross, Cecil; Shah, Chirag; Torres, Marcela; Fu, Chieh-Lin 'Kathy'; Rucker, Karen; Pinciaro, Paul; et al.
Aim: To evaluate the safety and efficacy of 10% intravenous immunoglobulin (IVIG; Flebogamma ® 10% DIF) in individuals with chronic immune thrombocytopenic purpura (ITP).Patients & methods: Patients aged 3–70 years, diagnosed with chronic ITP, received 1 g/kg IVIG over two consecutive days.Results: 64 evaluable patients (51 adults, 13 children) with chronic ITP received IVIG. The primary efficacy end point (increased platelet counts from ≤20 × 10 9 /l to ≥50 × 10 9 /l by day 8) was achieved by 81.3% of patients; mean time to response was 1.7 days (all responders). Adverse events, mostly mild or moderate, were reported in 59 patients (92.2%).Conclusion: Flebogamma ® 10% DIF administered over two consecutive days was safe and effective in adults and children with chronic ITP.